1997
DOI: 10.1007/s002530050985
|View full text |Cite
|
Sign up to set email alerts
|

Development of a low-cost fermentation medium for ethanol production from biomass

Abstract: Nutrient cost is an important aspect in the fermentation of biomass to ethanol. With a goal of developing a cost-effective fermentation medium, several industrially available nutrient sources were evaluated for their effectiveness in the simultaneous saccharification and fermentation of pretreated poplar with Saccharomyces cerevisiae D5A. These studies showed that a low-cost medium containing 0.3% corn steep liquor and 2.5 mM MgSO4 7H2O was similar in performance to a nutrient-rich medium. Besides its low cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(44 citation statements)
references
References 4 publications
1
43
0
Order By: Relevance
“…Hence, extra costs due to external nutrient supplement are deemed unavoidable (Kadam and Newman, 1997). Unlike most cellulosics, corn distiller's dried grains with solubles (DDGS) is a nutrient-rich feedstock derived from the corn-based ethanol industry (Spiehs et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, extra costs due to external nutrient supplement are deemed unavoidable (Kadam and Newman, 1997). Unlike most cellulosics, corn distiller's dried grains with solubles (DDGS) is a nutrient-rich feedstock derived from the corn-based ethanol industry (Spiehs et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The ability to generate and convert fermentable sugars from lignocellulosic materials to ethanol in a cost-effective fashion is the central technological challenge to fully unlock its commercial potential (3). Unfortunately, fermentation of hydrolysates derived from pretreated lignocellulosic biomass is often preceded by washing (4), nutrient supplementation (5,6), and detoxification (7,8), which are very costly processes (9,10). The fermentability of a hydrolysate is strongly dependent on the feedstock pretreatment and strain selection.…”
mentioning
confidence: 99%
“…It was also previously reported that the addition of activated carbon is effective in promoting C. krusei IA-1 growth in repeated cultivations using spent media, 18 and that it is possible to reuse spent media by adding activated carbon, 19 with the aim of reducing the cost of raw materials. 20,21 Therefore, coupling fermentation processes employing C. krusei IA-1 in the presence of activated carbon with pervaporation using silicone rubber-coated silicalite membranes would cost-effectively provide reliably refined bioethanol.…”
Section: Resultsmentioning
confidence: 99%
“…To lessen the deterioration in pervaporation performance during bioethanol separation, CSL and peptone concentrations in fermentation broths should be maintained at low values (reducing the associated cost of the medium) but at concentrations that can give a high ethanol production rate. 20 Figure 4 shows the effects of succinate addition on pervaporation performance. The decreased performance is clearly different from those observed following the addition of nutrients such as peptone, yeast extract, and CSL.…”
Section: Effects Of Components In Fermentation Broths On Pervaporatiomentioning
confidence: 99%